UPAYA PENINGKATAN PENDIDIKAN MELALUI PROGRAM MENGAJAR DI SEKOLAH DI KAMPUNG GUNUNG LEUTIK DESA BENTENG KABUPATEN BOGOR - Widyastuti, Hardiana; Damari, Arfan; Zahra, Nisa; Ermawati, Wita Juwita; Firdaus, Guntur (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Bogor Regency is one of the districts that has a high dropout rate in basic education. The average dropout rate occurs at the junior high school level, one of which has occured in Benteng Village, especially Gunung Leutik Village, Bogor. The high dropout rate in 2018 showed that the 9-year basic education goals stated in the 1945 Constitution have not been realized. As a form of community service, the academic community of the Management Department, Faculty of Economics and Management, IPB University in collaboration with SMP Negeri 1 Ciampea and the Nusa Educator Community organized a program named “teaching activities in schools”. The program was held for sixth months, started on August 16, 2021 - January 14, 2021. The activity was initiated by Thematic Community Service Program activities / KKN-T (a regular program of IPB University Students) that was continued by ‘teaching in schools’ program. This program taken place in Mount Leutik Village. Teaching at this school was carried out to students from Open Middle School, Package B, and Package C. The Nusa Educator Community and the IPB University KKNT team carried out program planning, including acceptance and search for new students, preparation of teaching materials and the determination of teaching locations. Furthermore, socialization was carried out simultaneously to the community so that their children who are not yet in school are sent to school. The outputs of this activity were to increase the motivation of students who have dropped out of school to continue education until they graduate and provide knowledge for students so that they are able to achieve graduation according to their level and are able to increase graduation rates at the elementary, junior high, and high school levels in the local area.